The fetal fraction of cell-free DNA in maternal plasma is not affected by a priori risk of fetal trisomy - Brar, Herb; Wang, Eric; Struble, Craig; Musci, Thomas J.; Norton, Mary E. (The journal of maternal-fetal & neonatal medicine, 2013)
Objective: To determine the relationship between a priori risk for fetal trisomy and the fraction of fetal cell-free DNA (cfDNA) in maternal blood. Methods: A comparative analysis on fetal cfDNA amounts was performed in subjects stratified into a priori risk groups based on maternal age, prenatal screening results, or nuchal translucency measurement. Results: Across the highest and lowest deciles within each group, there were no significant differences in the fetal cfDNA fraction. Conclusions: These data support the concept that non-invasive prenatal test performance as determined by fetal cfDNA fraction is not predicted to be different based on patient risk classification.